Analisis Pemberian Sanksi Administratif pada Kasus PT. Multazam Terkait Pengumpul dan Pengangkutan Limbah B3 - Ranita Ivana Hottaruli; Devitha Dwi Andini; Dita Safitri Nurwidihantari (Peneliti.net, 2023)
In 2015 PT. Multazam was founded as a company in the field of collecting and transporting B3 waste based in the city of Makassar. However, in 2017 PT. Multazam received an administrative sanction lawsuit from the government for violating environmental regulations which caused serious environmental and health problems. This is caused by the collection and transportation of hazardous and toxic B3 waste. Administrative sanctions gave caused suspension and revocation of business licenses. Therefore, there is a need for strict supervision and law enforcement to prevent environmental violations and ensure environmental sustainability and public health.